Evaluation of potential hybridazion between native fish and invasive bleak Alburnus alburnus - Sousa-Santos, C. (2019)
Background. Freshwater fishes are among the most threatened taxa worldwide. The proliferation of introduced species in the Iberian Peninsula is currently one of the main drivers of native fish declines. One of such species, the bleak, Alburnus alburnus (Linnaeus, 1758), has become widespread in the last 25 years and, due to its phylogenetic proximity, poses a high risk of hybridization with native species. The aim of this study was to improve the current knowledge on this issue by 1) evaluating the presence of hybrids with Alburnus alburnus in the wild, using molecular screening of individuals representing the intermediate morphology and 2) testing if artificial crosses between Alburnus alburnus and the highly threatened native cyprinid Anaecypris hispanica (Steindachner, 1866) resulted in viable hybrid offspring. Material and methods. The genetic profile of Alburnus alburnus was established using the cytochrome b and beta-actin genes to allow comparisons with the profiles of the sympatric species with which it could potentially hybridize: Anaecypris hispanica; Squalius alburnoides (Steindachner, 1866); and Squalius pyrenaicus (Günther, 1868). This profile was further used to assess if fish with the intermediate morphological features were indeed hybrids. Finally, artificial crosses between Alburnus alburnus and Anaecypris hispanica were conducted to test the viability of the offspring. Results. Alburnus alburnus individuals were genetically identical to the stocks introduced in Spain and the Czech Republic. A reference library composed of 15 species-specific nDNA loci was built and used to characterize wild fish showing intermediate morphological features. Results showed that Alburnus alburnus is currently hybridizing with males and females of Squalius alburnoides and that morphometric identification is insufficient for a reliable detection of the hybrids. Artificial crosses between the bleak and the highly threatened Anaecypris hispanica did not result in viable offspring. Conclusion. Phylogenetic relatedness, traduced in the absence of pre- and post-zygotic barriers to reproduction, together with other factors related to the ecology and life history of the species involved are essential for hybridization to occur. As such, the proliferation of the bleak through the Iberian hydrographical network represents a serious additional threat for the already imperilled native Squalius and Anaecypris species. Keywords: hybridization risk, invasive fish species, biodiversity loss, conservation